Accurate calculation of aerodynamic coefficients of parafoil airdrop system based on computational fluid dynamic. (25th April 2018) - Wu, Wannan; Sun, Qinglin; Luo, Shuzhen; Sun, Mingwei; Chen, Zengqiang; Sun, Hao
Accurate calculation of canopy aerodynamic parameters is a prerequisite for precise modeling of a parafoil airdrop system. This investigation analyses the aerodynamic performance of the canopy in airdrop testing combining the leading-edge incision and the trailing-edge deflection. Aerodynamic parameters of the canopy are obtained using the computational fluid dynamic simulations, and then, the output data are used to estimate the deflection and incision factors. The estimated lift and drag coefficients instead of the traditional parameters based on lifting-line theory are incorporated into the eight degrees of freedom dynamic model of an airdrop system and make some simulations. The effectiveness of the proposed method for calculating aerodynamic coefficients is verified by actual airdrop testing.